Avaliação da qualidade ambiental no complexo estuarino da baía de São Marcos – margem Equatorial Amazônica - DJALO, Cadijatu (2021)
The present study aims to evaluate the environmental quality of the external portion of the São Marcos Bay Estuarine Complex (CESM), based on the determination of metal levels in the sediment and changes in the structure and distribution of the benthic macrofauna community in relation to standards rainfall in the region. To this end, collections were carried out in 3 periods of the year (end of rain - FC, beginning of rain - IC, and end of drought - FS), distributed in 12 sampling points, during the neap tide. Physico-chemical parameters of water, such as temperature, salinity, hydrogen potential (pH), and dissolved oxygen (DO) were determined in situ using a CTD, while suspended particulate matter (MPS) were determined in the laboratory using a gravimetric technique. The sediment samples were collected with the aid of the Gibbs model dredger and used for analysis of redox potential (Eh), pH, particle size, % organic matter – OM, metals (Al, Fe, Mn, Cu, Zn) and benthic macrofauna. Metal concentrations were determined by Induced Plasma Optical Emission Spectrometry (ICP-OES) according to analytical method D:2014 and the preparation of samples following EPA 3051 A: 2007 and EPA 6010. Counting and identification of organisms were carried out (down to the lowest possible taxonomic level) with the aid of a binocular magnifying glass, optical microscope and identification keys whenever necessary. As a result, it was possible to observe through the physical-chemical parameters of the water the influence of different water masses (temperature and salinity) in relation to local seasonality, with a predominance of coastal waters in FS and FC and estuarine or brackish waters in IC. Metal concentrations in the sampled area, with the exception of point 8 (P8*), were not significantly different between periods, however, lower concentrations of all elements were observed in the IC where metal was detected. presence of the estuarine water mass. Regarding the spatial distribution of metals, it was possible to observe a significant difference between the southern portion (PS) and the northern portion (PN) of the study area, with the highest concentrations being found in PS, which presented a predominance of fine sediments and high levels of OM. , regardless of the period sampled. The elements Al and Fe, as well as MO, were the main geochemical carriers of the other metallic elements. The sediment quality indices revealed different levels of enrichment (FE) and contamination (IGEO) by the metals analyzed, which reveal contributions of anthropic origin, in addition to the contribution lithogenic, mainly in the northern portion of the study area (PN) and in P8*. It is noted that in PN, there was significant enrichment of Fe and Cu, and moderate enrichment of Mn, Cu and Zn, varying depending on the period of the year. Regarding the degree of metal contamination, IGEO identified that metal contamination varied from low to high, and exhibited a pattern similar to that revealed by the FE, where it is identified that the PN and P8* are being more impacted than the PS. Analysis of benthic macrofauna shows that the most abundant taxonomic groups were Tanaidacea, Polychaeta, Nematoda, Gastropoda, Amphipoda and Oligochaeta. Species (Capitella capitata, Capitella sp.), opportunistic class (oligochaetes) and order (tanaidacea) were also identified in the present study, revealing the possible existence of environmental stressors. The distribution of organisms as a whole was affected by particle size, MO, Eh and metal concentration. Environmental descriptors, such as the Shannon Diversity Index, Margalef Richness, Pielou Evenness, and the Marine Biotic Index (AMBI), revealed that the region's benthic community is poor in diversity and richness, and is in imbalance, the environment being classified as slightly polluted in most cases. Extreme environmental pollution situations were reported by AMBI only in PS in FS, and in P8* in FS and FC. Therefore, through the results obtained, it is concluded that in general, the PN is enriched in metals, presenting inferior quality in terms of geochemical indexes and the biological integrity of the region.